Solo Baru Modern Music Concert HallPenekanan pada Arsitektur Kontemporer - Fitrianto, Diky; , Dr. Ir. Qomarun, MM; , Nur Rahmawati S, ST, MT (2016)
Solo Baru is a region in Central Java and is a satellite city directly adjacent to the city of Solo, but was included in the district of Sukoharjo. This satellite city more appropriately dubbed the "city of the elite", because the buildings here are very modern and fairly luxurious, somewhat contrary to Solo condensed feel of Java. Music concert hall is a building that serves to hold a music concert or live music performances. In accordance with its objectives, the main technical matters required are acoustics in the concert hall, both objective and subjective conditions must be optimal, in accordance with the demands of musicians and audience. The concert hall is the result of architectural innovation of the western culture that technically it is intended to support the culture of the art of music. Its history began in the early 19th century began with the building in the form of amphitheater, colloseoum, the new opera house and then the concert hall. This development is also in line with the development of the science of acoustics and architecture. In modern times, the concert hall has been the result of the latest innovations of various technologies, science and art of music it self.